KANTUNG POLYURETHANE DAN KEJADIAN HIPOTERMIA PADA BAYI BERAT BADAN LAHIR RENDAH - Rahmawati, Viki; Hastuti, Sari; Muslihatun, Wafi Nur (Jurnal Kesehatan Ibu dan Anak, 2013)
Polyurethane bag is a heat retaining pockets draft for LBW which made of airtight until the neck and cover the vody of the baby. Open air flow accelerates the onset for hypothermia LBW faster heat loss, especially in convection. 35% LBW occurred during hypothermia delivery to the NICU. Modification design of SAC during the polyurethane covering method of sending to the NICU aims to minimize the risk of hypothermia on LBW. The purpose of this research to find out the influenced of polyurethane bag against gen hypothermia on LBW in RSUD Wonosari by 2013. Type of research design is experimental quasi post test with control groups. Location research is in the maternity and perinatal space of RSUD Wonosari. The sampling technique use purposive criteria of the 32 respondents, divide 2 groups, 4 groups of treatment (LBW using polyurethane bag) and 16 controls groups (not using a polyurethane bag). Result: used Chi-Square p-value 0,01 <0,05 OR 0,1 (CI 95% 0,0 ? 0,7), there is a polyurethane bag influence on LBW. LBW using a polyurethane bag has a risk of suffering hypothermia 1 times lower than LBW not using a polyurethane bag.